Manufacturing Mesenchymal Stromal Cells for the Treatment of Osteoarthritis in Canine Patients: Challenges and Recommendations - Ivanovska, Ana; Wang, Mengyu; Arshaghi, Tarlan Eslami; Shaw, Georgina; Alves, Joel; Byrne, Andrew; Butterworth, Steven; Chandler, Russell; Cuddy, Laura; Dunne, James; Guerin, Shane; Harry, Rob; et al. (Frontiers in Veterinary Science, 2022)
The recent interest in advanced biologic therapies in veterinary medicine has opened up opportunities for new treatment modalities with considerable clinical potential. Studies with mesenchymal stromal cells (MSCs) from animal species have focused on in vitro characterization (mostly following protocols developed for human application), experimental testing in controlled studies and clinical use in veterinary patients. The ability of MSCs to interact with the inflammatory environment through immunomodulatory and paracrine mechanisms makes them a good candidate for treatment of inflammatory musculoskeletal conditions in canine species. Despite the absence of clear regulatory frameworks for veterinary advanced therapy medicinal products, there has been an increase in the number of commercial cell-based products that are available for clinical applications, and currently the commercial use of veterinary MSC products has outpaced basic research on characterization of the cell product. In the absence of quality standards for MSCs for use in canine patients, their safety, clinical efficacy and production standards are uncertain, leading to a risk of poor product consistency. To deliver high-quality MSC products for veterinary use in the future, there are critical issues that need to be addressed. By translating standards and strategies applied in human MSC manufacturing to products for veterinary use, in a collaborative effort between stem cell scientists and veterinary researchers and surgeons, we hope to facilitate the development of quality standards. We point out critical issues that need to be addressed, including a much higher level of attention to cell characterization, manufacturing standards and release criteria. We provide a set of recommendations that will contribute to the standardization of cell manufacturing methods and better quality assurance.